Absolute vs. relative poverty and wealth: Cooperation in the presence of between-group inequality - Eugenio Levi; Abhijit Ramalingam (Masaryk University, Faculty of Economics and Administration, 2023)
While inequality in resource endowments has been shown to affect cooperation levels in groups, much of this evidence comes from studies of within-group inequality. In an online public goods experiment, we instead examine the effects of payoff-irrelevant inequality in resources between groups on cooperation within equal groups. When all groups are poor or rich, their contribution behaviour is very similar. Relative inequality, when poor and rich groups coexist, leads to lower contributions in rich groups. Our results suggest that this is related to a combination of within- and between-group inequality aversion and to stereotypes about the rich contributing less than the poor
Keywords: C72; C91; C92; D63; H41; 330; between-group; resource inequality; cooperation; public goods; online experiment; beliefs